Value addition of red beet (Beta vulgaris L.) by‐products: Emulsion formation and stability. (17th July 2018) - Ralla, Theo; Salminen, Hanna; Wolfangel, Timo; Edelmann, Matthias; Dawid, Corinna; Hofmann, Thomas; Weiss, Jochen
Summary: Replacement of synthetically derived food additives and increase of sustainability are two major trends within the food industry, and usage of by‐products may represent a potential solution. We characterised an extract obtained from red beet that could also be obtained from red beet peels, that are typical industrial by‐products, and examined its interfacial and emulsion forming properties. Results showed that red beet extract contained considerable amounts of surface‐active saponins. The smallest negatively charged droplets (~1.36 μm, −40 mV) were obtained at low emulsifier‐to‐oil ratio and were fairly stable over a wide range of environmental stresses such as a wide pH range and temperature (<50 °C) despite some oiling‐off. Emulsions showed flocculation at low pH, as well as coalescence at high temperature (≥50 °C) and phase separation after a freeze–thaw cycle. Overall, our results indicate red beet extract may be employed as new naturally derived emulsifier for food and beverage products. Abstract : Red beet extract as a new naturally‐derived emulsifier.